Almost Shakespeare – But Not Quite. Issue 2 (1st June 2021) - Jones, Keith
Abstract: Taking Emily St. John Mandel's Station Eleven and Gary Schmidt's Wednesday Wars as test cases, this article explores generic considerations in modern novels that employ Shakespeare but do not retell or recast the plot of any particular work by Shakespeare. Questions to be considered include how the works employ the Shakespearean genres of comedy, tragedy, history, romance and tragicomedy to create their own genres – and, conceivably, to transcend them. The article will also consider the mainstream appropriation of Shakespeare in Mandel and Schmidt. The Three Fates by Linda Lê will be briefly examined as a less straightforward reworking of the material of a single Shakespeare play ( King Lear ).